1989
DOI: 10.1017/s0043174500071988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watering Frequency, Drought, and Glyphosate on Growth of Field Bindweed (Convolvulus arvensis)

Abstract: Greenhouse experiments were conducted to determine effects of watering frequency, drought stress, and a combination of watering frequency and glyphosate on growth of field bindweed. Watering daily, twice weekly, or weekly to field capacity affected field bindweed grown from seed differently than plants grown from root runner segments. Shoot and root dry matter of plants grown from seed increased when plants were watered frequently but dry matter allocated to root runners did not change when plants were watered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…First, the cuticular layer has been proposed to be the major barrier to foliar herbicide uptake (Bukovac 1976). Field bindweed (Convolvulus arvensis L.) that grows in arid regions, compared with humid regions, generally is more difficult to control.The decreased level of control was attributed to a smaller leaf area and increased cuticle thickness under arid conditions (Dall'Armellina & Zimdahl 1989). Westwood et al (1997) also reported that glyphosate-resistant field bindweed, with a greater amount of cuticle, absorbed less glyphosate than sensitive plants under the condition of low relative humidity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the cuticular layer has been proposed to be the major barrier to foliar herbicide uptake (Bukovac 1976). Field bindweed (Convolvulus arvensis L.) that grows in arid regions, compared with humid regions, generally is more difficult to control.The decreased level of control was attributed to a smaller leaf area and increased cuticle thickness under arid conditions (Dall'Armellina & Zimdahl 1989). Westwood et al (1997) also reported that glyphosate-resistant field bindweed, with a greater amount of cuticle, absorbed less glyphosate than sensitive plants under the condition of low relative humidity.…”
mentioning
confidence: 99%
“…Field bindweed ( Convolvulus arvensis L.) that grows in arid regions, compared with humid regions, generally is more difficult to control. The decreased level of control was attributed to a smaller leaf area and increased cuticle thickness under arid conditions (Dall'Armellina & Zimdahl 1989). Westwood et al.…”
mentioning
confidence: 99%
“…The variability in phenotypes potentially would further influence the expected level of glyphosate efficacy. Reduced efficacy of glyphosate has been reported in several weed species under cool and dry conditions (Dall’Armellina and Zimdahl 1989; Jordan 1977; Masiunas and Weller 1988; Reddy 2000).…”
Section: Introductionmentioning
confidence: 99%
“…El control de las malezas en zonas áridas generalmente es más dificultoso que en las regiones húmedas, y ello se puede atribuir, en el caso de los herbicidas de postemergencia, a una menor área foliar y a un incremento en la capa cuticular bajo condiciones de déficit hídrico (Dall´Armellina and Zimdahl, 1989). Westwood et al…”
Section: Características Morfológicas Que Confieren Tolerancia a Los unclassified
“…Es probable que la presencia de abundantes tricomas en la superficie foliar de G perennis provea atributos de protección, además de morigerar el impacto de las condiciones Existe información que demuestra que el control de malezas presentes en zonas áridas generalmente es más dificultoso que en las regiones húmedas, y ello se puede atribuir a una menor área foliar y a un incremento en la capa cuticular en condiciones secas (Dall´Armellina and Zimdahl, 1989). Estos antecedentes y la presencia de abundantes tricomas con teicodes asociados podrían explicar uno de los principales mecanismos de tolerancia que presenta G. perennis a la aplicación del glifosato.…”
Section: Peso Seco Yemas -Córdobaunclassified